Correlation of Hematological Toxicity with the Bone Marrow Radiation Dose and Volume during Concurrent Chemo Radiation in Patients with Cervical Cancer - Sagar, Ragavendra D; Madabhavi, Irappa; Revannasiddaiah, Swaroop (Asian Pacific Journal of Cancer Care, 2021)
Aims & Objective: Hematological toxicity is common in patients with cervical cancer treated with concurrent chemo radiotherapy (CT-RT), so the purpose is to assess this hematological toxicity and correlate the toxicity with the dose and volume of bone marrow included in the field of radiation. Materials & Methods: Twenty five patients with histologically proven cervical cancer attending to our Cancer centre from July 2018-August 2019 were the subjects of this study. Patients were treated on 6 MV linear accelerator with a radical intent with concurrent chemotherapy using cisplatin 50 mg weekly. The planning CT was done for all the patients before the treatment and contouring of the pelvic bone marrow apart from other organs at risk was done. Hematological toxicity was assessed using RTOG common toxicity criteria weekly during and at 2 weeks after the completion of the treatment. Results: A total of 25 patients on CT-RT treatment were assessed. Sixteen patients were in locally advanced stage. The variation in HB, TLC, Platelets, and ANC counts from the baseline to 2 weeks after chemo radiotherapy were assessed. Grade II anemia was observed in 12 and Grade III in 2 patients. There were no toxicity as far as WBC and platelets were considered. There was also no correlation between the volume of bone marrow included in the field of irradiation and appearance of anemia. Conclusion: CT-RT for cervical cancer is safe and is associated with minimal hematological toxicity in the form of anemia. The toxicity is same for different volumes of bone marrow included in the field of irradiation with both 3DCRT as well as IMRT technique. The toxicity observed is probably contributed by Cisplatin.